Diversity of Dengue Virus Serotype in Endemic Region of South Sulawesi Province. (23rd April 2018) - Taslim, Muh.; Arsunan, A. A.; Ishak, Hasanuddin; Nasir, Sudirman; Usman, Andi Nilawati
Abstract : The objective of this research was to investigate serotype diversity pattern of dengue hemorrhagic fever virus by using real-time-polymerase chain reaction (RT-PCR) method. It was an explorative laboratory research in endemic dengue fever area in South Sulawesi Province, Indonesia, that is, Makassar municipality and Maros and Gowa region. Serological examination was carried out using real-time-polymerase chain reaction (RT-PCR) method to determine the serotype of dengue virus. The data showed that, of 30 patients, 20 patients (66.67%) were from Makassar municipality: 10 patients (33.33%) from Gowa region and 10 patients (33.33%) from Maros region. The serotypes found were DENV-2 and DENV-4 and no DENV-1 and DENV-3 serotypes were found. Makassar municipality and Gowa region have higher infection with serotype DENV-2, that is, 40% of cases compared with Maros, which is 20.0%. Statistical test results showed no significant differences between the three endemic areas. Maros region has the highest infection with serotype DENV-4, that is, 40% of cases compared with Makassar municipality (5.0%) and Gowa region (0%). Statistical test results showed significant differences between the three endemic areas. This result revealed that serotypes obtained in endemic areas of dengue fever in South Sulawesi are DENV-2 and DENV-4 and not serotypes DENV-1 and DENV-3. Makassar municipality has DENV-2 and DENV-4 serotype, infection dominated by DENV-2, while Maros region also has DENV-2 and DENV-4, but DENV-4 is the dominant serotype. Gowa municipality only has DENV-2 serotype infection.